Identifikasi Jenis Aves Diurnal di Sawah Bergas Lor Tengah Kabupaten Semarang - Galih Kholifatun Nisa’; Moch Argo Setyoko (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2021)
Rice fields are one of the wetland ecosystems that have a variety of components in it. One of biotic components found in rice fields is birds. This study aims to identify the type of diurnal birds in the Bergas Lor rice fields of Semarang Regency, Central Java. Observations were carried out in the morning and in the evening in August 2020. The data collection technique used was the purposive sampling method. The results showed that there were 19 species of birds from 13 families. The birds found were mostly grain-eating birds because the observation location was in the form of rice fields.